LOS BRAQUIÓPODOS DEL CARBONÍFERO SUPERIOR DE LA QUEBRADA LARGA, EN LAS CABECERAS DEL RIO BLANCO, PROVINCIA DE SAN JUAN (Ameghiniana, 2013)
The brachiopods from the "Formación Quebrada larga" of the Quebrada Larga, province San Juan, Argentina is herein described. The presence of Heteralosia cornelliana (derby ) is reported for the first time in Argentina, and the identity of Buxtonia riojana (Leanza ) is discused. The gastropods, brachiopods and plant remains present in this formation can be refered to the Upper Carboniferous.